Analysis of Judgment Conditions in Making a Decision for Rehabilitation of Persons of Criminal Actions Based on Narcotics ABUSE Decision Number: 302/PID.SUS/2022/PN. TJK and Decision Number 217/PID.SUS/2022/PN.KLA - Asep Hidayatulloh; Xie Guilin; Deng Jiao; Yuanyuan Wang (Yayasan Adra Karima Hubbi, 2023)
Background. Problems in handling cases of criminal acts of narcotics abuse, namely the emergence of criminal disparities in terms of sentencing, such as in cases of criminal acts of narcotics abuse in Decision Number: 302/Pid.Sus/2022/PN. Tjk and Decision Number 217/Pid.Sus/2022/PN.Kla. Purpose. What are the factors that cause differences in judges' legal considerations in imposing decisions on rehabilitation of perpetrators of narcotics abuse based on Decision Number: 302/Pid.Sus/2022/PN. Tjk and Decision Number 217/Pid.Sus/2022/PN.Kla. What are the legal considerations of judges in making decisions on rehabilitation of perpetrators of narcotics abuse based on Decision Number: 302/Pid.Sus/2022/PN. Tjk and Decision Number 217/Pid.Sus/2022/PN.Kla. Method. The research was carried out using a normative juridical approach and an empirical approach. The data used in this study were secondary data obtained from library materials, and field research was carried out by observation and interviews (interviews). The data obtained were analyzed qualitatively and juridically and deductively concluded. Results. the factors that cause differences in judges' considerations in imposing decisions are sourced from the legal system and sentencing philosophy, sourced from judges, and sourced from defendants. The occurrence of disparity is also due to the factor that the Panel of Supreme Court Justices has different legal considerations and the principle of judging themselves so that there is a different application of Articles from Court Decisions of first level and appellate level.: 302/Pid.Sus/2022/PN. Tjk and Decision Number 217/Pid.Sus/2022/PN.Kla. Conclusion. Suggestions in this study are that the Panel of Judges in cases of criminal acts of narcotics abuse should minimize criminal disparities to prevent the development of a negative perspective of society towards the criminal system in judicial institutions.